De Jaufre Rudel à la littérature en langue d’oïl : échos du topos de l’amor de lonh et poétique de la mémoire affective - Luminiţa Diaconu (Revue des Langues Romanes)
Our analysis aims to highlight some of the particular nuances which enriched the troubadours’ tradition in the XIIth-XIIIth centuries, when many trouveres enjoyed embroidering their verses with the topoï attached to fin’amor, or even borrowing them directly from the Occitan auctoritas. Explicit references to some well known troubadours, as well as quotations inserted into larger narratives such as the Roman de Guillaume de Dole (or The Romance of the Rose) bear witness to this phenomenon. Our attention will be focused on reverberations of Jaufre Rudel’s creation in the North, especially those about the amor de lonh topos. In our opinion, this is an authentic mise en abyme in the Roman de Guillaume de Dole, considering the multiple reflections of Rudel’s verses, essentially linked to imperative of remembrance, and to narrative framework, even if the insertion of Occitan coblas is accompanied, moreover, by a questioning about literary canons and, finally, by notable mutations in this schema of imaginary.